2008
DOI: 10.1086/592850
|View full text |Cite
|
Sign up to set email alerts
|

Allergies: Their Role in Cancer Prevention

Abstract: The nature of the biological relationships between cancers and allergies has intrigued researchers and health care providers for five decades. Three hypotheses have been proposed: antigenic stimulation predicts positive associations between cancers and allergies (i.e., allergy sufferers are more likely to get cancer), whereas immunosurveillance and prophylaxis predict inverse associations (i.e., allergy sufferers are less likely to get cancer). Immunosurveillance predicts inverse associations for cancers of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
1
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 104 publications
3
109
1
11
Order By: Relevance
“…Whether this is because of a stronger reaction of the immune system of HGG patients on environmental influences (compared with LGG patients) or vice-versa is at this stage only speculative. However, our result supports the observation of Sherman et al (35) who noted that an inverse association with allergies were more often found for cancer of different tissues, including brain tissue, and organ systems that interface with external environment than in those tissue that do not so. The site specificity of the association between allergies and cancer is also described in a review by Merill et al (2007) (36).…”
Section: Discussionsupporting
confidence: 93%
“…Whether this is because of a stronger reaction of the immune system of HGG patients on environmental influences (compared with LGG patients) or vice-versa is at this stage only speculative. However, our result supports the observation of Sherman et al (35) who noted that an inverse association with allergies were more often found for cancer of different tissues, including brain tissue, and organ systems that interface with external environment than in those tissue that do not so. The site specificity of the association between allergies and cancer is also described in a review by Merill et al (2007) (36).…”
Section: Discussionsupporting
confidence: 93%
“…A possible explanation for this reduction in risk is that the hyperactive immune system of allergic individuals leads to increased surveillance and, thereby, protection against development of pancreatic cancer cells [71] .…”
Section: Allergiesmentioning
confidence: 99%
“…Three distinct perspectives underpin the possible association of atopy with cancer. According to the ''antigenic stimulation'' hypothesis, atopic inflammation contributes to cancer by causing oxidative damage that activates mutations in tumor suppressor genes or post-translational modifications in proteins involved in DNA repair or apoptotic control [5][6][7]. Conversely, the ''immune surveillance'' theory proposes that atopy is a consequence of a generalized enhanced immune responsiveness that has the capability to detect and eradicate dysregulated cells.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the ''immune surveillance'' theory proposes that atopy is a consequence of a generalized enhanced immune responsiveness that has the capability to detect and eradicate dysregulated cells. An inverse association between cancer and allergy is also predicted by the ''prophylaxis'' hypothesis, by which allergic reactions frequently expel mutagenic toxins, microorganisms and environmental contaminants, promote tissue repair, and encourage behavioral avoidance of irritants and toxins antigens [7]. Nonetheless, reports that allergies associate with either reduced or increased risk of cancer are collectively inconsistent [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation